2015
DOI: 10.48550/arxiv.1511.05959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergent Perturbation Theory for the lattice $ϕ^4$-model

Abstract: The standard lattice perturbation theory leads to the asymptotic series because of the incorrect interchange of the summation and integration. However, changing the initial approximation of the perturbation theory, one can generate the convergent series. We study the lattice φ 4 -model and compare the operator φ 2 n calculated using the convergent series and obtained by Monte Carlo simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…The previous studies of the convergent series application to the lattice φ 4 -model [27] demonstrated a critical slow down of the convergence rate with the increasing of the lattice volume V (see Section V). However, this problem can be resolved by the following observation.…”
Section: Variational Seriesmentioning
confidence: 83%
See 1 more Smart Citation
“…The previous studies of the convergent series application to the lattice φ 4 -model [27] demonstrated a critical slow down of the convergence rate with the increasing of the lattice volume V (see Section V). However, this problem can be resolved by the following observation.…”
Section: Variational Seriesmentioning
confidence: 83%
“…However, a rigorous mathematical proof of the convergence of expansions [21][22][23]26] is still missing. A non detailed version of the rigorous construction of the convergent series similar to [22,23] for the one-dimensional lattice φ 4 -model was presented in [27]. The numerical computations within the convergent series in [27] revealed a perfect agreement with the results obtained by the Monte Carlo simulations for the lattice with the volume V = 2 and demonstrated slow convergence to the correct answers even for the slightly bigger lattices (with V = 4 and V = 8 lattice sites).…”
Section: Introductionmentioning
confidence: 88%
“…Recently, the convergent series similar to [18,19] was derived for the real action models defined on finite lattices [25,26]. There the restriction to a finite amount of degrees of freedom provided the conditions, enough to carry out the construction mathematically rigorously and to prove the possibility to express coefficients of the convergent series for any model on the finite lattice with the real action and an even degree polynomial interaction as linear combinations of SPT-terms.…”
Section: Introductionmentioning
confidence: 99%
“…In recent works [18,3,4] the convergent series for the real and certain complex action models defined on finite lattices was constructed in a rigorous way. It was shown there that the application of the dimensional regularization can be interpreted as an additional re-summation procedure accelerating the series convergence.…”
Section: Introductionmentioning
confidence: 99%